Energy assessment of an R134a refrigeration plant upgraded to an indirect system using R152a and R1234ze(E) as refrigerants. (5th July 2018) - Sánchez, D.; Cabello, R.; Llopis, R.; Catalán-Gil, J.; Nebot-Andrés, L.
Highlights: An energy quantification of converting a direct expansion system to an indirect one is presented and discussed. The experimental analyses have been performed with a commercial refrigerating plant for medium temperature. Indirect system was performed with three refrigerants: R134a, R152a and R1234ze(E). Results showed an average increment in energy consumption of 22.6%. The refrigerant mass charge was reduced up to 62% depending on the refrigerant used. Abstract: In this work the experimental results obtained from a direct expansion refrigerating plant converted into an indirect plant, are presented and discussed in terms of energy consumption for a commercial refrigerating unit plugged to a medium temperature cabinet. Refrigerants used in the analysis are R134a for direct system, and R134a, R152a and R1234ze(E) for indirect system. The evaluation has been performed at laboratory conditions using three different heat rejection levels: 43.6, 32.8 and 23.3 °C keeping constant the environmental conditions in the cabinet (25 °C; 55%). From the experimental tests performed during 24 h, it has been demonstrated that the adoption of an indirect configuration results in an increment of the total energy consumption of the refrigerating plant regardless the refrigerant adopted. The average increment registered was 21.8% for R134a, 18.7% for R152a and finally 27.2% for R1234ze(E). The adoption of an indirect system also reduces the refrigerant mass charge of the facility up to 62% depending on the refrigerant used.